Analysis of the Establishment, Development and Future of Agricultural Reconversion - Carlos E. Romo Bacco; Neftalí Parga-Montoya; M. del Carmen Montoya Landeros; Héctor A. Cortés-Palacios; Marisela Y. García Vidales (Journal of Human, Earth, and Future)
Economic, social, and crop management and environmental factors are important for the development and establishment of successful productive units. The objective of this study was to evaluate the interactions between the characteristics of productive units and the perceptions of producers. Different areas of performance were considered in the establishment of lemon and avocado crops in the municipality of Calvillo, Aguascalientes, Mexico.49 agricultural producers who carried out productive reconversion of their parcels for the establishment of lemon and avocado crops were interviewed. Semi-structured surveys were applied to evaluate the characteristics of the management and operation of the agricultural farms. Likewise, the perceptions of producers were measured in the economic (ECO), social (SOC), and environmental (CULT/AMB) areas. Through a PERMANOVA and binary logistic models, the groups of variables analyzed were simultaneously analyzed. The areas analyzed (ECO, SOC, and CULT/AMB) were found to be significantly affected (p<0.001) by the source of water, the expectations of continuity of the farms, and the crop prior to productive reconversion. The novelty of these findings demonstrates the importance of decision-making for the establishment of alternative crops in the search for higher incomes by agricultural producers and to ensure the continuity of productive farms for the development of rural areas.